Double–Contrast‐Enhanced Sonography for Diagnosis of Rectal Lesions With Pathologic Correlation. (1st April 2014) - Lu, Man; Yan, Brain; Song, Jun; Ping, Wu; Yue, Lin-Xian; Song, Bin
Abstract : Objectives: Transabdominal sonography with a gastrointestinal contrast agent has been widely used in China for investigation of digestive disorders. Double–contrast‐enhanced sonography combines a gastrointestinal luminal contrast agent with an intravenous contrast agent for imaging of lesions. The purpose of this pilot study was to assess the value of double–contrast‐enhanced sonography for preoperative diagnosis of rectal lesions. Methods: We conducted a prospective single‐center study using double–contrast‐enhanced sonography of rectal lesions. Patients were administered both rectal and intravenous contrast agents, and imaging was performed transabdominally, transanally, and transrectally. Morphologic characteristics and perfusion parameters were compared between histologically proven adenocarcinomas, adenomas, and inflammatory masses. Perfusion parameters were analyzed with time‐intensity curves, measuring the contrast arrival time, time to peak, peak intensity, and area under the curve of the lesions and normal rectal tissue. Results: From January 2009 to September 2012, 420 patients were recruited, with 227 patients meeting inclusion/exclusion criteria and having 232 rectal lesions analyzed (172 rectal adenocarcinomas, 45 adenomas, and 15 inflammatory masses). Adenocarcinomas had variable enhancement patterns. Adenomas were all hypoenhanced in a homogeneous pattern. Inflammatory masses had a hyperenhanced rim with no central enhancement. Time‐intensity curve perfusion parameters (arrival time, time to peak, peak intensity, and area under the curve) of rectal adenocarcinomas, adenomas, and inflammatory masses were significantly different compared to normal rectal tissue ( P < .05). The differences in the arrival time, peak intensity, and time to peak among the different lesions were also significant ( P < .05). Conclusions: Double–contrast‐enhanced sonographic assessment of morphologic enhancement patterns combined with vascularity parameters may help differentiate benign and malignant rectal lesions.